Contributions from Alfred Schütz's phenomenological sociology for nursing research - review article - Marcio Wagner Camatta; Cíntia Nasi; Diego Schaurich; Jacó Fernando Schneider (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2008)
Understanding the human being is a complex task, because it involves biological, psychological and social questions. Investigation of Cartesian procedure had suffered ruptures, mainly because of the criticism to objectivity, on dealing whit human questions. In the end of nineteen century, phenomenology is born as a philosophical-methodological option for research, in which Comprehensive Sociology, from Alfred Schütz, outstands. This study's objective is discuss some of the possible contributions from Schütz's Phenomenological Sociology for nursing research. The main concepts boarded were intentionality, intersubjectivity, determined biographical situation, human actions, typification and social relation. Phenomenological research seeks the meanings that people attribute to their own experience, which are revealed with these people's descriptions. Alfred Scütz's phenomenological sociology aims the subjective meaning of the human actions, trying to establish the ideal type by typification. These concepts can be used as a theoretical-methodological base to investigate about things lived in the social world, mainly when it is about a social world in which nursing professionals are part of.